Insectivorous Birds: Tharangambadi Seashore and Adjoined Places as the Potential for Feed - Subramaniyan , Sivakumar; Ganesan , Thomas Nithiyanandam (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The birds which are forage in wetlands are likely to be insectivores. Due to the course of the life cycle of insects, the birds have an enormous amount of feed for their survival. The study revealed that, diversity and distribution of birds in relation to the insect diversity in Tharangambadi Sea shores, Mayiladuthurai District, Tamil Nadu from January 2017 to December 2017. The total count method was employed for the observation of birds. Collection of the insect by the scooping nets in the aquatic environment and quartets in the terrestrial environment was used. The results showed that 56 species of birds were encountered from 14 orders. Among the 56 species of birds, insectivores (41%) dominated followed by carnivore (20%), piscivore (14%), omnivore (11%), granivore (9%), frugivore (3%) and nectivores (2%). The insectivorous bird's species richness was high in the season post-monsoon (23) followed by Monsoon (22), pre-monsoon (20), and summer (19). The abundance was high during the post-monsoon (797) followed by monsoon (756), pre-monsoon (372), and summer (279) (F= 4.059; p<0.01). Simultaneously, the insect species richness was high during the season of post-monsoon, monsoon, pre-monsoon (19), and summer (18). The abundance was high during the post-monsoon (545) followed by monsoon (430), pre-monsoon (399), and summer (377) (F=0.5647; p>0.01). The insects and insectivorous birds' species richness and abundance were correlated positively. It concluded that insectivorous avian diversity and abundance were high during the insects’ abundance and diversity. Therefore, the Tharagambadi seashore is a potential habitat for insectivorous birds.